Research Brief #17: Agricultural Diversity and Child Nutrition in Nepal. - Shively, Gerald.; Sununtnasuk, Celeste; Thapa, Ganesh. (Tufts University. Tisch Library., 2016)
This brief investigates empirical connections between agriculture and child nutrition in Nepal. The authors augment the standard approach to explaining child nutrition outcomes by including information about household level agricultural production characteristics, including indicators of agricultural diversity. Keywords: Nutrition Innovation Lab, Research Brief.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy